Sociocultural and structural determinants of healthcare-seeking of people affected by leprosy in Sierra Leone’s Western area: a qualitative study - Alexandra Asboeck; Lansana Hassim Kallon; Fabian Schlumberger; Matthew Willis; Anil Fastenau; Anja Krumeich (Tropical Medicine and Health)
Abstract Background Leprosy, a neglected tropical disease, remains a major global health concern. If left untreated, it can lead to permanent disabilities and severe social stigma, profoundly impacting the well-being of those affected and their families. Leprosy is a public health concern in Sierra Leone, affecting hundreds of people each year. A significant number of individuals are already living with disabilities at the time of diagnosis, indicating delays in detection and treatment. These delays contribute to a vicious cycle of poverty, social exclusion, and long-term health complications. Methods This study employed a qualitative approach to explore healthcare-seeking behaviors among people affected by leprosy in Sierra Leone’s Western Area. Eighteen semi-structured interviews were conducted with individuals affected by leprosy, traditional healers, and community health workers in the Western Area of Sierra Leone in May and June 2024. An inductive thematic analysis was used to identify key patterns and factors influencing healthcare-seeking decisions. This methodology provided an in-depth understanding of the sociocultural and systemic barriers affecting early diagnosis and treatment. Results The study found that healthcare-seeking behavior is shaped by factors at the individual, community and healthcare system levels. Individually, misconceptions about leprosy, stigmatization and financial hardship delay care. Social attitudes in communities reinforce stigmatization and isolation. At the healthcare system level, poor access, limited services, and economic motives hinder treatment. These factors, compounded by widespread poverty, create significant obstacles to timely diagnosis and care. Conclusions The complex interplay of individual, societal, and healthcare-related factors underscores the need for a multi-faceted approach to improving leprosy care in Sierra Leone. Multi-dimensional strategies involving people affected, traditional healers, healthcare workers, community leaders and public health policymakers are needed to address the factors contributing to diagnostic delays. Strengthening community awareness, integrating traditional healing practices with biomedical medicine, and enhancing healthcare accessibility and affordability are critical to ensuring early detection and reducing the burden of leprosy in Sierra Leone.